A Rare Pediatric Case of Posttraumatic Pseudoaneurysm: Case Report and Literature Review. Issue 12 (December 2019) - Gu, Ada; Kam, April J.
Abstract : Abstract: Posttraumatic pseudoaneurysms are extremely rare in pediatric populations. In many cases, pseudoaneurysms may be confused with abscesses, epidermoid cysts, arteriovenous fistula, foreign objects, and ganglion cysts, as well as tumors. They are associated with distinguishing findings of "pulsatile mass, a palpable thrill, and an audible to-and-fro murmur" (1), which can be confirmed by various imaging techniques. In this report, we describe the case of a 4-year-old boy who presented to the pediatric emergency department 3 weeks after falling and subsequently getting cut by glass. Upon clinical examination, the patient presented with pulsatile, swollen mass in the left wrist. A Doppler ultrasound of the left wrist demonstrated that the area of clinical concern in the left wrist showed a pseudoaneurysm, and prominent arterial blood flow was seen within the pseudoaneurysm. Because pseudoaneurysms, particularly posttraumatic pseudoaneurysms, are extremely rare in the pediatric population, it may be easy to miss these cases during clinical examination. Misdiagnosis of the pseudoaneurysm can cause delayed treatment, a longer recovery period, and complications such as infection, rupture, and hemorrhage. It is important for physicians to consider this entity when evaluating patients with symptoms of asymptomatic bulges to painful pulsatile masses after trauma.